The contribution of love, and hate, to organizational ethics - Schwartz, Michael (College teacher); Harris, Howard (Head of Management Research); Comer, Debra R., 1960- (Bingley, U.K. : Emerald, 2016)
Ideally suited to researchers, postgraduates and professionals interested in key issues such as tax avoidance and corporate privacy, the latest volume of Research in Ethical Issues in Organizations examines how profit seeking and not for profit organizations can be conceived and designed to satisfy legitimate human needs in an ethical and meaningful way. The volume addresses a range of contemporary issues in applied and professional ethics and explores the unique role of organizational ethics in creating and sustaining a pluralistic, free enterprise economy.
Love and hate in organizational ethics / Michael Schwartz, Howard Harris, Debra R. Comer -- Divine friendship and the practice of management / Jim Wishloff -- Let love rule: opportunities and impediments for cooperation in network organizations / Erik Groeneveld, Leon van den Dool -- Surviving and thriving in constructive conflict: the emotional lives of business ethics faculty and non-profit human service workers / Jana Craft, Mary Godwyn -- Love and hate in university technology transfer: examining faculty and staff conflicts and ethical issues / Clovia Hamilton, David Schumann -- Can the understanding of economics lead to conscious sustainability? the example of love / Mario Carrassi -- For the love of family: a mafia lens on love and commitment / Janine Pierce, Benjamin Pierce -- Beating swords into plowshares to realize the potential of the UNGC: using appeasement to constrain the arms industry / Michael Schwartz, Debra R. Comer -- An assessment model for business commitment to culture and fine arts: application to the Spanish IBEX 35 listed companies / Rafael Cejudo, Pablo Rodri<U+0301>guez-Gutie<U+0301>rrez -- Value creation as business commitment to responsible consumption / Cristina Neesham, Susan Freeman -- Hemingway, A. (2014). Corporate social entrepreneurship: integrity within. Cambridge, UK: Cambridge University Press / Howard Harris -- Bititci, U. (2015) Managing business performance: the science and the art. Chichester, UK, John Wiley & Sons / Howard Harris -- Visser, W. (2015) Sustainable frontiers: unlocking change through business, leadership and innovation. Sheffield, UK, Greenleaf Publishing Limited / Lars Moratis -- McManus Warnell, J. (2015). Engaging millennials for ethical leadership: what works for young professionals and their managers. New York, NY: Business Expert Press, LLC.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Business Ethics; Business ethics; Business & management; Economics, finance, business & management; Business ethics; Professional ethics